Mon’s Embroidery Cloth : Guidelines for Conservation and Value-Added Creation in a Creative Economy - Phon-in, Thanida (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objectives of the research article were study economic conditions and problems. Presenting conservation guidelines and adding value to the embroidery cloth of Mon Ladkrabang community. The operation consists of procedures for collecting information from relevant documents non-participant observation Interview with key informants and a group discussion meeting to present conservation ideas and create added value. The analysis of documentary material and interpretation was used to generate interview summaries as study tools. The operating results showed that Mon community has a long history a way of life that is tied to the river agriculture and with the faith in Buddhism, resulting in a beautiful embroidery pattern. It is a potent cultural product. Can generate income and well-being for the family of the Mon community. But still lack of promotion from related agencies in the area of ​​conservation Promotion of the production process and adding value to the product.